2023
DOI: 10.3389/feart.2023.1150954
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy assessment of various supervised machine learning algorithms in litho-facies classification from seismic data in the Penobscot field, Scotian Basin

Satya Narayan,
Suresh Konka,
Akash Chandra
et al.

Abstract: Litho-facies classification is an essential task in characterizing the complex reservoirs in petroleum exploration and subsequent field development. The lithofacies classification at borehole locations is detailed but lacks in providing larger coverage areas. The acquired 3D seismic data provides global coverage for studying the reservoir facies heterogeneities in the study area. This study applies six supervised machine learning techniques (Random Forest, Support Vector Machine, Artificial Neural Network, Ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…ANN is an intelligent computing system comprising several elements combined across a weighted connection to solve complex problems related to optimization, prediction, modeling, etc. , It is inspired by the biological nervous system of the brain, in which neurons are mimicked by artificial neurons (connected units or nodes) of the ANN system. The linkage between the neurons decides the functioning of the system.…”
Section: Methods and Workflowsmentioning
confidence: 99%
“…ANN is an intelligent computing system comprising several elements combined across a weighted connection to solve complex problems related to optimization, prediction, modeling, etc. , It is inspired by the biological nervous system of the brain, in which neurons are mimicked by artificial neurons (connected units or nodes) of the ANN system. The linkage between the neurons decides the functioning of the system.…”
Section: Methods and Workflowsmentioning
confidence: 99%
“…Some previous studies have demonstrated the advantages of machine learning algorithms [10,11]. Consequently, some machine learning techniques are widely employed in MPM and related domains [12,13].…”
Section: Introductionmentioning
confidence: 99%